Implementation of Differentiated Learning Styles to Improve Analysis of Poetry Elements For Class X Students of SMA Negeri 22 Surabaya - Abdur Rahman Haidar; Fransisca Dwi Harjanti; Siti Umiati (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The aim of this research is to observe the development of students' learning outcomes in dealing with poetry material by applying differentiated learning strategies and identifying students' learning styles and seeing how differential learning strategies, especially product differentiation, influence the mastery of students in class X.1 SMA Negeri 22 Surabaya to poetry material. The research was conducted using a qualitative descriptive approach. Data is collected through observation, document analysis, and assessment of students' work. The research results show that students display 3 types of learning styles: visual, auditory, and kinesthetic. The differential learning strategy applied is product differentiation, which allows students to express their understanding of poetry through different works. The implementation of this learning succeeded in achieving mastery above the minimum passing score (KKM) of 75, with a score range of 75-100. Assessment of student attitudes from the Pancasila Student Profile also provides scores in the same range. The implication of this research is that the use of differential learning strategies, especially product differentiation, can be an effective approach in teaching poetry material in high school. Identifying students' learning styles is also important in designing learning that suits their needs. In this way, teachers are able to pay more attention to the diversity of students in the learning process, increase their mastery of the material, and strengthen the expected attitude values, for example those reflected in the Pancasila profile.